The Relationship between Knowledge, Attitude, and Practice of Iron Supplementation and the Incidence of Anemia - Silaban, Hertina; Gracia Tennes, Josephine; Simarmata, Vidi Posdo A (Rifa'Institute, 2025)
Introduction: Anemia is a major health problem among women of reproductive age, including female university students, and iron tablet consumption is an important preventive measure. Objective: To analyze the relationship between knowledge, attitudes, and practices of iron tablet consumption and anemia among female medical students. Method: An analytical cross-sectional study was conducted involving 84 female medical students from the 2023 cohort at University X, selected through convenience sampling. Data were collected using a structured questionnaire on knowledge, attitudes, and practices of iron tablet consumption, and hemoglobin levels were measured by finger-prick tests. The relationship between independent variables and anemia status was analyzed using the chi-square test. Result and Discussion: Most respondents had good knowledge and positive attitudes, but unsatisfactory practices regarding iron tablet consumption. Higher knowledge, more positive attitudes, and appropriate practices were associated with a lower prevalence of anemia, indicating a gap between what students know and what they actually do. Conclusions: Knowledge, attitudes, and practices of iron tablet consumption showed a significant relationship with anemia incidence, so targeted interventions are needed to improve adherence to iron tablet consumption among female students.